Management of PFO in paradoxical embolic stroke with hemorrhagic conversion: a case report - Sabina, Michael; Khanani, Aqeel; Tsai, Joshua; Rigdon, Amanda; Massaro, Joseph (Frontiers in Cardiovascular Medicine, 2024)
A paradoxical embolism is defined as a venous thrombus that crosses through a heart defect, into the systemic circulation, usually through a patent foramen ovale. Treatment varies between closure of patent foramen ovale versus medical management based on a variety of individual risk factors and the cardiac defect's characteristics. We describe a case of paradoxical stroke complicated by hemorrhagic conversion, ultimately requiring an IVC filter.